Antioxidant and cytotoxic activities of 2-oxo-1,2,3,4-tetrahydropyrimidines - Sarosh Iqbal; Shahida Perveen; M. Iqbal Choudhary; Musarrat Jabeen; Shumaila Kiran; Faiza Qayyum; Khalid Mohammed Khan (Results in Chemistry)
Oxidative stress (OS) is an imbalance between ROS and antioxidants which is caused by increased synthesis and buildup of reactive oxygen species as well as a reduced ability to detoxify them. It contributes to the onset and progression of chronic inflammation, cancers, diabetes mellitus, atherosclerosis, Alzheimer’s disease, ocular disease, nephropathy, and premature aging. The molecules known as antioxidants contribute significantly to both the prevention and exaggeration of ailments. In the present study, heterocyclic ethyl esters of 2-oxo-1,2,3,4-tetrahydropyrimidines 1–25 were assessed for their antioxidant activity by employing two robust in vitro bioassays; superoxide anion, and DPPH radical scavenging assays. Cytotoxicity was also performed to evaluate the cytotoxicity on PC3 cells. Out of twenty-five, twenty-two compounds exhibited IC50 values in the range of 3.32 ± 0.08 – 167 ± 0.7 µM in superoxide anion assay. Compound 2 (IC50 = 3.32 ± 0.08 µM) remained the most potent as compared to quercetin dihydrate (IC50 = 94.1 ± 1.1 µM). Whereas, compound 10, possessing a catechol moiety was identified as an excellent dual radical scavenger. Hence, this study identified 2-oxo-1,2,3,4-tetrahydropyrimidines ethyl esters as non-cytotoxic, potent ROS scavengers that can be studied further to treat oxidative stress and related pathologies.